PENGARUH BRAND IMAGE, BRAND AWARENESS, DAN BRAND AMBASSADOR DALAM PROMOSI K-POP TERHADAP MINAT PEMBELIAN ULANG PADA PRODUK SCARLETT DENGAN SIKAP MEREK SEBAGAI VARIABEL MEDIASI - Hidayah, Mahabbatul; Kussudyarsana, Kussudyarsana (POLITEKNIK LP3I JAKARTA, 2026)
The purpose of this study is to examine how brand image affects, brand awareness, and brand ambassadors on repurchase intention of Scarlett products, with brand attitude as a mediating variable. This research used a causal research design with a quantitative approach. Data was gathered using questionnaires given out to 180 individuals who regularly use Scarlett products in Indonesia.had made repeat purchases, and were aware of Scarlett’s promotions involving K-Pop brand ambassadors. Purposive sampling was the method of sampling that was employed. Using SmartPLS 4 software, partial least squares–structural equation modeling, or PLS-SEM, was used to analyze the data. The findings show that while brand awareness and image have a favorable and considerable impact on brand attitude, they do not significantly affect repurchase intention. Both brand attitude and repurchase intention are significantly and favorably impacted by brand ambassadors. Additionally, repurchase intention is positively and significantly impacted by brand sentiment. Brand attitude strongly mediates the association between brand image and brand ambassador on repurchase intention, according to mediation tests, but it does not mediate the impact of brand awareness. These findings emphasize the crucial role of brand attitude in encouraging repurchase intention, particularly through positive brand perceptions and the effectiveness of K-Pop brand ambassadors.